2021
DOI: 10.3390/molecules26164773
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Tea Brewing Parameters on the Antioxidant Potential of Infusions and Extracts Depending on the Degree of Processing of the Leaves of Camellia sinensis

Abstract: The polyphenol content of tea depends on the growing region, harvest date, the production process used, and the brewing parameters. In this study, research was undertaken that included an analysis of the influence of the brewing process parameters on the content of total polyphenols (Folin-Ciocalteu), epigallocatechin gallate (HPLC), and antioxidant activity (against DPPH radicals) of fresh tea shrub leaves grown from Taiwan and of teas obtained from them (oolong, green in bags, and green loose from the spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 31 publications
1
10
0
4
Order By: Relevance
“…According to the DPPH and ABTS assays, a longer brewing time and higher brewing temperature resulted in an increasing antioxidant capacity, while a higher water-to-tea ratio and longer brewing time resulted in a weaker antioxidant capacity. These results were consistent with some previous findings [ 45 , 46 ]. Gan, P.T.…”
Section: Resultssupporting
confidence: 94%
“…According to the DPPH and ABTS assays, a longer brewing time and higher brewing temperature resulted in an increasing antioxidant capacity, while a higher water-to-tea ratio and longer brewing time resulted in a weaker antioxidant capacity. These results were consistent with some previous findings [ 45 , 46 ]. Gan, P.T.…”
Section: Resultssupporting
confidence: 94%
“…Different IC 50 values were recorded between brewing times. Excessive temperatures and boiling times destroyed the phenolics in the sample (Kowalska et al, 2021). The acetone extract group showed the highest antioxidant activities.…”
Section: Antioxidant Activitymentioning
confidence: 96%
“…Some studies suggest that green tea ( Camellia sinensis ) supplementation protects against wrinkles by increasing collagen and elastin fiber levels and inhibiting the production of MMP-3 in the skin ( Kowalska et al, 2021 ). Recent studies have reported that green tea can activate autophagy by increasing the activity of PI3 kinase and BECLIN-1 ( Prasanth et al, 2019 ).…”
Section: Autophagy Inducers: An Alternative Option In Preventing Skin...mentioning
confidence: 99%